ANTIDIABETIC ACTIVITY OF KALANCHOE PINNATA IN ALLOXAN-INDUCED DIABETIC RATS - OPHELIA GEORGE, LATHA; HR, RADHA; BV, SOMASHEKARAIAH (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The main purpose of the present study was to analyze the antidiabetic activity of methanolic extract of the leaf of Kalanchoe pinnata in alloxan-induced diabetic rats. Methods: Diabetes mellitus (DM) is a chronic metabolic and endocrine disease regarded as a serious global public health problem. Albino Wistar rats were divided into four groups. Group I (normal) received drinking water throughout the course till 20 days. Groups II-IV received alloxan (120 mg/kg b.w) i.p on the 1st day of the study period. Group III animals received glibenclamide (10 mg/kg p.o) and Group IV received K. pinnata (200 mg/kg b.w p.o) for 20 days. The body weight, blood glucose level, serum urea, blood urea nitrogen (BUN), creatinine, cholesterol, total protein (TP), uric acid, and tissue (liver) antioxidant parameters: Malondialdehyde (MDA) and glutathione (GSH) were measured. Results: K. pinnata treated rats showed the percentage increase in the body weight, decrease in the blood sugar level, creatinine, TP level, urea, uric acid, and BUN, MDA, and GSH when compared to alloxan-induced diabetic mellitus control rats. Thus, K. pinnata could be possibly employed to treat DM. Conclusion: This preliminary analysis tested the most promising profile. It seems that methanolic extract of the leaf of K. pinnata improved general, blood serum, and liver antidiabetic agent. However, further studies confirming its potential is certainly warranted.